Предмет: Математика,
автор: kurbanovaarian
(3,6x + 2,5) - (1,8x + 2,3) = 1,6x
Решить уравнение, с решением и подсчетами пожалуйста
Ответы
Автор ответа:
0
(3,6х+2,5)-(1,8х+2,3)=1,6х
3,6х+2,5-1,8х-2,3=1,6х
1,8х-1,6х=-0,2
0,2х=-0,2
х=-0,2:0,2
х=-1
Ответ: -1
3,6х+2,5-1,8х-2,3=1,6х
1,8х-1,6х=-0,2
0,2х=-0,2
х=-0,2:0,2
х=-1
Ответ: -1
Автор ответа:
0
3.6х+2.5-1.8х-2.3=1.6х
3.6х-1.8х-1.6х=2.3-2.5
0.2х=-0.2/:0.2
х=-1
3.6х-1.8х-1.6х=2.3-2.5
0.2х=-0.2/:0.2
х=-1
Похожие вопросы
Предмет: Немецкий язык,
автор: Anfisa2010
Предмет: Алгебра,
автор: pipkina1973
Предмет: Математика,
автор: romasastanin94
Предмет: Алгебра,
автор: Nafox